1980
DOI: 10.3109/00048678009159380
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Young Women who have Attempted Suicide

Abstract: Findings from a questionnaire assessment of depression in three groups of young women whose suicide attempts were of widely differing medical lethality are reported. No significant difference in the degree of depression between patients whose suicide attempt required intensive care unit resuscitation, those who required some cautionary medical observation, and those whose attempt produced negligible physical effect was found. Furthermore, on the basis of a decision-rule applied to their questionnaire responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The extreme opposite is also possible. In their review of 23 studies, Goldney and Pilowsky [37] found that, when using objective rating scales, depression was diagnosed at double the rate compared with when clinical judgement was used. As a diagnosis of depression in the current study was based on clinical judgement, an underestimation of its prevalence is also a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme opposite is also possible. In their review of 23 studies, Goldney and Pilowsky [37] found that, when using objective rating scales, depression was diagnosed at double the rate compared with when clinical judgement was used. As a diagnosis of depression in the current study was based on clinical judgement, an underestimation of its prevalence is also a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In screening for suicide, depression is regarded as the major risk factor (Joiner et al, 2005; Marttunen et al, 1991; Goldney and Pilowsky, 1981; Cohen-Sandler et al, 1982; Vandivort and Locke, 1979) but not sufficient to cause suicidal behavior (Apter et al, 1995). Substance abuse is a strong disinhibiting factor (Blumenthal, 1988; U.S.…”
Section: Introductionmentioning
confidence: 99%
“…substance abuse and other psychiatric disorders amongst the patient group may have accounted for the over-inclusiveness of this self-report measure. I n considering this issue it is pertinent t o note 64 DEPRESSION AND ATTEMPTED SUICIDE: A COMPARATIVE STUDY the discussion of Goldney and Pilowsky [45] centred on the finding ofa high rate of depression as measured by the LPD in 104 young women who had attempted suicide. The authors stated that the allocation of one third of this group to the LPD category "endogenous" depression did not indicate that these patients had a clinical diagnosis of endogenous depression, but rather that they appeared to have vegetative or biological features which have been said to comprise part of the clinical picture of endogenous depression and that they were so allocated by the LPD questionnaire.…”
Section: Discussionmentioning
confidence: 99%